2019
DOI: 10.2106/jbjs.18.01096
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Femoral Component Sagittal Positioning and Anterior Knee Pain in Total Knee Arthroplasty

Abstract: ScottThe purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
3
29
0
2
Order By: Relevance
“…As patellar resurfacing could result in several complications, such as fracture, loosening, and dislocation 19,20 , many surgeons prefer to not perform patellar resurfacing in TKA. Though not clearly understood, there are many reasons for the AKP, such as infrapatellar fat pad excision, the design and position of the implant, the size and rotation of the trochlear groove, and the surgical technique 21,22 . Theoretically, blocking superficial sensory nerves around the patella could reduce the incidence of AKP and improve the knee function after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…As patellar resurfacing could result in several complications, such as fracture, loosening, and dislocation 19,20 , many surgeons prefer to not perform patellar resurfacing in TKA. Though not clearly understood, there are many reasons for the AKP, such as infrapatellar fat pad excision, the design and position of the implant, the size and rotation of the trochlear groove, and the surgical technique 21,22 . Theoretically, blocking superficial sensory nerves around the patella could reduce the incidence of AKP and improve the knee function after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Overstuffing risks higher joint reaction forces, patella fracture, reduced range of motion and anterior knee pain; understuffing risks a reduction in knee extension strength, extensor lag and instability [ 52 ]. Despite these theoretical risks, recent clinical studies correlating radiographic appearance and clinical outcomes have been mixed [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Selecting the components of the appropriate size in total knee arthroplasty (TKA) is essential to providing patients with the best possible outcome. Inappropriate component positioning and sizing affects range of motion, soft-tissue balancing, stability, soft-tissue irritation, and impingement [ [1] , [2] , [3] ]. Previous studies have demonstrated that accurate component sizing can be difficult, particularly in women.…”
Section: Introductionmentioning
confidence: 99%